2017
DOI: 10.1177/1557988317693346
|View full text |Cite
|
Sign up to set email alerts
|

The Priorities of Iranian Male Adolescents Health Needs

Abstract: Health in the adolescence period guarantees the next generation’s health. The assessment of health needs is the first stage for the implementation of health promotion interventions. This study aimed to assess the priorities of male adolescent’s health needs in Tehran, Iran, in year 2015. This cross-sectional correlational study was conducted with 1,200 male adolescents aged between 13 and 18 years. Single male adolescents studying in public guidance and high schools in Tehran, Iran, in year 2015 were chosen us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…In this regard, the result of a study in Iran has indicated that 28% of male adolescent aged 15-18 years have had sexual experience before the marriage [21]. Moreover, Zare et al (2017) reported that sexual health had been the main health needs of adolescent boys in Iran [22]. Despite the essential need of sexual health education for Iranian adolescents, there are no school-run programs in their educational curriculum yet [23]; thereby many of adolescents do not obtain proper sexual education in schools.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the result of a study in Iran has indicated that 28% of male adolescent aged 15-18 years have had sexual experience before the marriage [21]. Moreover, Zare et al (2017) reported that sexual health had been the main health needs of adolescent boys in Iran [22]. Despite the essential need of sexual health education for Iranian adolescents, there are no school-run programs in their educational curriculum yet [23]; thereby many of adolescents do not obtain proper sexual education in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Puberty is the most important turning point in adolescence, which is the transition period from childhood to adulthood and the time to gain fertility. This period is caused by the activation of the sexual glands and is accompanied by a series of symptoms and physical and mental changes [3,6]. How to deal with puberty and the puberty process are important issues that need to be addressed by the authorities and parents.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, from the perspective of Iranian men, sexual and reproductive health is described in terms of three concepts of needs, responsibilities, and social norms affecting these aspects of their health; majority of men report difficulties in accessing related health service centers and increasing their awareness in this area. Although there are no accurate estimates on the utilization of sexual and reproductive health services in Iran, evidence suggests that access to sexual and reproductive health services and utilization of these services in the country is limited [22]; therefore, the sexual and reproductive needs of men, especially younger men, rank higher than other health-related needs [23]. Men's concern about their needs to promote their sexual and reproductive health as emphasized in this study has been also reported by other studies [24].…”
Section: Discussionmentioning
confidence: 99%